Insomnia: An important antecedent impacting entrepreneurs' health - Ludvig Levasseur; Jintong Tang; Masoud Karami (Journal of Risk and Financial Management, 2019)
Insomnia (and sleep deprivation) has an important impact on multiple outcomes such as individuals' cognitive abilities, decision-making, and affect. In this paper, drawing from sleep research, we focus on entrepreneurs' insomnia-health relationship and test a serial mediation model that considers entrepreneurs' insomnia as an important predictor of their poor health. More specifically, we hypothesize that insomnia heightens entrepreneurs' stress, which leads to increased negative affect, which ultimately undermines their health conditions. Using a sample of 152 Iranian entrepreneurs, we found support for our hypotheses as our results suggest that insomnia has a positive (and detrimental) effect on poor health (via more stress and negative affect). Contrary to research calls focused on stress reduction as one performance improvement mechanism, our results suggest sleep quality as a more effective mechanism for entrepreneurs to reduce their stress and to improve their health. Theoretical and practical implications, limitations, and directions for future research are also discussed.
Keywords: 330; insomnia; stress; negative affect; health; entrepreneurs